Implicit Microfoundations for Macroeconomics - Ian Wright (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
A large market economy has a huge number of degrees of freedom with weak microlevel coordination. The 'implicit microfoundations' approach considers this property of micro-level interactions to more strongly determine macro-level outcomes compared to the precise details of individual choice behavior; that is, the 'particle' nature of individuals dominates their 'mechanical' nature. So rather than taking an 'explicit microfoundations' approach, in which individuals are represented as 'white-box' sources of fully-specified optimizing behavior ('rational agents'), we instead represent individuals as 'black box' sources of unpredictable noise subject to objective constraints ('zero-intelligence agents'). To illustrate the potential of the approach we examine a parsimonious, agent-based macroeconomic model with implicit microfoundations. It generates many of the reported empirical distributions of capitalist economies, including the distribution of income, firm sizes, firm growth, GDP and recessions.
Keywords: A12; B41; C63; D50; E11; P16; 330; Microfoundations; macroeconomics; aggregation; power laws; Mikroökonomische Fundierung; Agent-based Model; Aggregation; Makroökonomik; Marktwirtschaft; Wahrscheinlichkeitsrechnung; Theorie